KINERJA KEUANGAN DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Annisa Annisa; Ika Wulandari (JURNAL ILMIAH EDUNOMIKA, 2025)
This research was conducted to determine and analyze the effect of financial performance and good corporate governance mechanism on the timeliness of financial report submission in manufacturing companies listed on the Indonesia Stock Exchange for the period 2022-2024. The population of this study was all manufacturing companies listed on the Indonesia Stock Exchange for the period 2022-2024. The sample of this study was taken using a purposive sumption technique. The analysis tool used Based on the data analysis and discussion that have been done previously, it can be concluded as follows, profitability does not affect the timeliness of financial reporting in manufacturing sector companies in the basic and chemical industry subsectors listed on the Indonesia Stock Exchange for the period 2022-2024. Managerial ownership has no effect on the timeliness of financial reporting in manufacturing companies in the basic and chemical industry subsector listed on the Indonesia Stock Exchange for the 2022-2024 period. Audit quality has no effect on the timeliness of financial reporting in manufacturing companies in the basic and chemical industry subsector listed on the Indonesia Stock Exchange for the 2022-2024 period.